Turbulence in River and Maritime Hydraulics - Davies, Peter A. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Understanding of the role of turbulence in controlling transport processes is of paramount importance for the preservation and protection of aquatic ecosystems, the minimization of the deleterious consequences of anthropogenic activity, and the successful sustainable development of river and maritime areas. In this context, the present Special Issue collects 15 papers which provide a representation of the present understanding of turbulent processes and their effects in river and maritime environments. The presented collection of papers is not exhaustive, but it highlights the key priority areas and knowledge gaps in this field of research. The published papers present the state-of-the-art knowledge of complex environmental flows which are useful for researchers and practitioners. The paper contents are an overview of some recent topics of research and an exposure of the current and future challenges associated with these topics.